Symbolic Interaction of Kyai and Santri in The Perspective of Ethical Leadership Based on Religious Values - Sarkowi, Sarkowi; Aisyah, Siti; Qosim, Roshiful Aqli (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Kyai is a key element in the growth and development of the pesantren community. The pesantren community under the leadership of Kyai is interesting to continue to be researched, one of which is in the aspect of symbolic interaction between kyai and santri which is unique in each pesantren. This research was conducted at Pondok Pesantren Nurul Huda (PPNH) Pondok Joyo Jember with a qualitative approach, focusing on the symbolic interaction between kyai and santri from a leadership perspective. The results showed that in his leadership, Kyai at Pondok Pesantren Nurul Huda (PPNH) strongly emphasized the cultivation of ethical religious values through symbolic interactions carried out with students. This is reflected in the form of interaction in all activities carried out by the Kyai with students who are very concerned with the side of religiosity and moral values. The pattern of interaction carried out with jismiyah, firkriyah, and ruhiyah so that it is able to form a meaning that manifests in the form of values and behavior of sincerity, simplicity, exemplary, assertiveness, and responsibility of students.